Visible Learning and synchronous online lesson in higher education: a study in engineering education. (2nd November 2022) - Bertozzi, Gabriele; Paciarotti, Claudia; Crivellini, Andrea
ABSTRACT: The Visible Learning (VL) approach to learning processes stems from Hattie's work based on synthesising meta-analyses regarding achievement in education. Although the model is used at many levels of instruction, its performance has been less studied in higher education, engineering education, and in the context of synchronous online learning in distance education. This study implements VL features and analyzes their ability to improve learning outcomes and teaching quality. To this end, a synchronous online lesson in a Fluid Dynamics course was implemented with 39 mechanical engineering students. The research method is a one-group pretest-posttest design and data were collected through a test and a 5-point Likert scale questionnaire. The learning achievement is measured using Cohen's d . The relevant effect size value obtained ( d  = 2.32) stands out from those in the literature where meta-meta-analyses report an impact on learning close to that of a traditional lecture ( d  = 0.08). Regarding the learning experience, students' ratings of both the lesson and the teacher's teaching quality are clearly positive. It can be concluded that the VL approach can produce significant learning gains and positive perceptions of instructional quality among students in the context of synchronous online instruction in engineering education.